2020
DOI: 10.1002/apj.2592
|View full text |Cite
|
Sign up to set email alerts
|

Flame front propagation and sinter strength properties of permeable sintering bed prepared via enhanced granulation with hydrated lime

Abstract: This paper is focused on investigating the influences of enhanced granulation with hydrated lime on the propagation of flame front and strength properties of the produced sinter in iron ore sintering. Pilot‐scale sinter pot experiments were performed at three hydrated lime levels, and the porous structures of sinter were reconstructed by high resolution X‐ray tomography. When hydrated lime increased from 0% to 2%, more permeable green bed with enlarged granule mean size and narrowed granule size distribution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Fan et al conducted simulations using artificial gas to analyze the influence of oxygen (O 2 ) content in circulating flue gas on the sinter bed [24]. Zhou and Zhou investigated the impact of granulation using hydrated lime on the sintering process and strength [25].…”
Section: Sintering Productivity Improvementmentioning
confidence: 99%
“…Fan et al conducted simulations using artificial gas to analyze the influence of oxygen (O 2 ) content in circulating flue gas on the sinter bed [24]. Zhou and Zhou investigated the impact of granulation using hydrated lime on the sintering process and strength [25].…”
Section: Sintering Productivity Improvementmentioning
confidence: 99%
“…The defined time was set based on the previous studies that reported that the duration that the sample is exposed to the maximum temperature is very short. 36,41,42) Figure 4 represents the conditions implemented for the sintering experiment. After the samples were cooled, one sample was supplied for XRD analysis to identify the major phases present in the standard sinter, and the other sample was analyzed in terms of wet chemical analysis to evaluate the amount of total Fe, metallic Fe and Fe 2 + .…”
Section: Sintering Process Of Ssm and Ssm Containing Cfsmentioning
confidence: 99%
“…Two main approaches can be distinguished, one of which is based on attempts to generate an imperfect shape of material structures from the data of the structure [ 9 , 10 , 11 , 12 ]. The second approach is to reproduce the shape as realistically as possible based on a material specimen [ 13 , 14 , 15 , 16 ]. In the case of the method based on realistic mapping, computer microtomography (micro-CT) is most frequently used [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%